Theoretical models of ordered alloys of thermoelectric materials based on Bi-Sb-Те - Manyk, О.М.; Manyk, T.O.; Bilynskyi-Slotylo, V.R. (Journal of Thermoelectricity, 2023)
Theoretical models of ordered alloys of promising thermoelectric materials of ternary systems based on Cd-Sb-Te have been developed.Using inverse triangulation methods, isothermal cross-sections and diagrams of the distribution of phase regions in ternary systems were constructed using binary state diagrams of the initial components (Cd-Sb; Cd-Te; Sb-Te).Calculations of the effective radii of interatomic interaction, electron density redistribution, and dissociation energy of the corresponding chemical bonds forming the Cd-Sb-Te crystal structure depending on the interatomic distances are presented.